2010
DOI: 10.1111/j.1743-6109.2009.01699.x
|View full text |Cite
|
Sign up to set email alerts
|

Erectogenic and Neurotrophic Effects of Icariin, a Purified Extract of Horny Goat Weed (Epimediumspp.) In Vitro and In Vivo

Abstract: Introduction Epimedium species (aka horny goat weed) have been utilized for the treatment of erectile dysfunction in Traditional Chinese Medicine for many years. Icariin (ICA) is the active moiety of Epimedium species. Aim To evaluate the penile hemodynamic and tissue effects of ICA in cavernous nerve injured rats. We also studied the in vitro effects of ICA on cultured pelvic ganglia. Methods Rats were subjected to cavernous nerve injury and subsequently treated for 4 weeks with daily gavage feedings of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(69 citation statements)
references
References 22 publications
2
64
0
3
Order By: Relevance
“…In another study by Yakubu et al [73], testes to body weight ratio in treated rats was found to be higher compared to control after 28 days of F. agrestis stem aqueous extract treatment (18,50, and 100 mg/kg), and the ratio remained unchanged after washout period of 10 days.…”
Section: Fadogia Agrestismentioning
confidence: 81%
See 1 more Smart Citation
“…In another study by Yakubu et al [73], testes to body weight ratio in treated rats was found to be higher compared to control after 28 days of F. agrestis stem aqueous extract treatment (18,50, and 100 mg/kg), and the ratio remained unchanged after washout period of 10 days.…”
Section: Fadogia Agrestismentioning
confidence: 81%
“…In the latest study, rats with cavernous nerve injury, treated with lowdose ICA also demonstrated significantly higher ICP/mean arterial pressure ratio. Immunohistochemistry and Western blot also showed significantly greater positivity for nNOS and calponin in penile tissues of all rats treated with ICA [18].…”
Section: Epimedium Herbs (Ying Yang Huo or Horny Goat Weed)mentioning
confidence: 85%
“…Recently, it was discovered that this enhancement is due to an inhibitory effect of both PDE4 and PDE5 by icariin [45] . Icariin was able to prevent fibrotic alterations in the corpus cavernosum after denervation in rats when administered daily by oral gavage [46] . Nutritional supplements such as antioxidants may reduce erectile tissue damage by radical oxygen species [47] .…”
Section: Pharmacotherapymentioning
confidence: 99%
“…The testosterone increases are statistically significant but arguably not clinically significant as of yet. Horny Goat Weed (Epimedium species) contains a compound(s) known as "icariin" that may have a PDE-5 like effect [232][233][234], but clinical research is needed because the majority of the impressive research was derived from basic science studies, but still it is also one clinicians should monitor. MACA (Lepidium meyenii) has some preliminary positive clinical data in fertility and ED, but needs more consistent research on standardization of active ingredients and efficacy, but is commonly used in other countries such as Peru [235,236].…”
Section: Resultsmentioning
confidence: 99%